PENGARUH WAKTU DAN SUHU PEMBAKARAN DALAM PEMBUATAN ABU DARI KULIT BUAH MARKISA SEBAGAI SUMBER ALKALI - Hari Surya Purnama; Herbert; Rondang Tambun (Talenta Publisher (Universitas Sumatera Utara), 2015)
The purpose of this study was to determine the optimum of combustion time and temperature of ash production from purple passion fruit peel (Parcilora idollis Sims f edulis Deg.). The experiment was begun to dry passion fruit peel, then combustion to obtaine the ash from passion fruit peel. The combustion was done by muffle furnace which time variables were from 1, 2, 3, 4, 5 hours and burning temperature variables were from 400 oC, 500 oC, 600 oC, 700 oC. The potassium that contained in ash have been extracted by distilled water with volume comparison was 1 : 10 for 24 hours. Observed responses were ash content, normality, pH, conductivity and potassium oxide content (% K2O). The best result of ash was in 5 hours with temperature 500 oC. The ash was analyzed by using AAS Atomic Absorption Spectroscopy, and 39,95 % of potassium oxide (K2O) content was obtained as maximum result.